Publisher Correction: In vivo neutralization of dendrotoxin-mediated neurotoxicity of black mamba venom by oligoclonal human IgG antibodies. Issue 1 (December 2018) - Laustsen, Andreas; Karatt-Vellatt, Aneesh; Masters, Edward; Arias, Ana; Pus, Urska; Knudsen, Cecilie; Oscoz, Saioa; Slavny, Peter; Griffiths, Daniel; Luther, Alice; Leah, Rachael; Lindholm, Majken; et al.
In the original version of this Article, the sixth sentence of the first paragraph of the Introduction incorrectly read 'Particularly, elapid antivenoms often have an unbalanced antibody content with relatively low amounts of antibodies against small neurotoxic venom components that have low immunogenicity, which often leads to low immune cgqtns in production animals8–10 '. The correct version states 'responses' instead of 'cgqtns'. This has been corrected in both the PDF and HTML versions of the Article.